The time is now for ubiquitous forensic mtMPS analysis. Issue 1 (31st May 2021) - Canale, Lauren C.; Parson, Walther; Holland, Mitchell M.
Abstract: Mitochondrial (mt) DNA sequence analysis is useful for assessing ancestral origin and migration, identifying human remains, and examining evidentiary material in forensic casework. Conventional Sanger‐type sequencing (STS) has been used for more than three decades to address these interests. This paper reviews the methodologies and merits of using a massively parallel sequencing (MPS) approach for mtDNA testing in forensic laboratories, as The Time is Now for Ubiquitous Forensic mtMPS Analysis . This article is categorized under: Forensic Biology > Haploid Markers Forensic Biology > Forensic DNA Technologies Abstract : mtMPS offers a sensitive and cost‐effective method, generating gigabases of sequence information from a single run, multiplexing target sequences that span all possibilities, and batching samples from different individuals. This invaluable methodology is now accessible to the average forensic laboratory.